2015
DOI: 10.1107/s2053230x15010407
|View full text |Cite
|
Sign up to set email alerts
|

Structure of α-carbonic anhydrase from the human pathogenHelicobacter pylori

Abstract: The crystal structure of α-carbonic anhydrase, an enzyme present in the periplasm of Helicobacter pylori, a bacterium that affects humans and that is responsible for several gastric pathologies, is described. Two enzyme monomers are present in the asymmetric unit of the monoclinic space group P21, forming a dimer in the crystal. Despite the similarity of the enzyme structure to those of orthologues from other species, the H. pylori protein has adopted peculiar features in order to allow the bacterium to surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The a-CA was shown to possess a periplasmic localization, the b-CA has been found in the cytoplasm, whereas no information is available on the expression/localization of the g-CA from this pathogenic bacterium 3,4,15,58,59 . It was suggested that the activity of periplasmic a-and b-CAs could be an additional requirement for the gastric colonization of the bacterium 57,60,61 . We want stress the fact that the primary sequence of the b-CA (HpyCAb) identified in the genome of H. pylori did not show a signal peptide at its N-terminal region when subject to the automated identification of the predicted signal peptide.…”
mentioning
confidence: 99%
“…The a-CA was shown to possess a periplasmic localization, the b-CA has been found in the cytoplasm, whereas no information is available on the expression/localization of the g-CA from this pathogenic bacterium 3,4,15,58,59 . It was suggested that the activity of periplasmic a-and b-CAs could be an additional requirement for the gastric colonization of the bacterium 57,60,61 . We want stress the fact that the primary sequence of the b-CA (HpyCAb) identified in the genome of H. pylori did not show a signal peptide at its N-terminal region when subject to the automated identification of the predicted signal peptide.…”
mentioning
confidence: 99%
“…Docking and molecular dynamic (MD) simulations were performed to study the binding mode of carvacrol and thymol in the active site of the α- and β-CA of Helicobacter pylori (HpCAα and HpCAβ) and β-CA of Malassezia globosa (MgCA). While the 3D coordinates of HpCAα (PDB 4XFW) [ 37 ] are available in the protein data bank, the X-ray solved structure of HpCAβ is not. Thus, comparative modelling was used to build a structural model based upon the known 3D coordinates of type I β-CAs from Synechocystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…Coordinating His residues were all within the expected bond length of 2.2 Å to Zn 2+ [89]. The active site appeared to be open and accessible to the solvent as observed in most CAs, with the catalytic pocket extending from the outside of the protein to the metal ion [34,90,91]. Validation results from various programs revealed that the structures modelled were of good quality (Table S5).…”
Section: Calculations Of Dimeric Models Of α-Cas and Their Validation Yields Good Quality Structuresmentioning
confidence: 85%